Design and Testing of Autonomous Chargeable and Wearable Sweat/Ionic Liquid‐Based Supercapacitors (Adv. Sci. 25/2022). Issue 25 (5th September 2022) - Selvam, Samayanan; Park, Young‐Kwon; Yim, Jin‐Heong
Abstract : Wearable Electronics In article number 2201890, Samayanan Selvam, Young‐Kwon Park, and Jin‐Heong Yim demonstrate ionic liquid electrolyte and sweat based dual electrolyte functioning supercapacitors capable of self‐charging ability. Typical planar structure electrodes are fabricated from tris(2‐aminoethyl)amine, poly‐3, 4‐ethylenedioxythiophene, and a graphene oxide mixture with copper‐mediated chelate. The supercapacitors are fabricated and attached directly to textile fabrics as well as flexible/stretchable film to apply their performance on the conformable human body during exercise with excellent energy harvest/storage performance and biocompatibility.